Plasma exchange is the hope for critically ill children with life-threatening autoimmune hemolytic anemia - Noha El-Anwar; Hafez Bazaraa; Fatma Abdel Maksoud; Yasmin Ramadan (SpringerOpen, 2024)
Abstract Background Autoimmune hemolytic anemia (AIHA) is a rare disease in children, sometimes associated with acute, life-threatening, rapidly progressive course requiring prompt management. The aim of our study is to describe the role and outcome of plasma exchange in the acute management of pediatric patients with AIHA requiring transfusion and refractory to high doses of corticosteroids. Methods This was a descriptive retrospective report of all patients admitted to the pediatric intensive care unit (PICU) of Children's University Hospital who received PE for acute intractable AIHA resistant to management with pulse steroids starting from June 2017 to June 2022. The demographic data, vitals, and laboratory investigations at PICU admission and upon discharge were gathered. The number of PE sessions needed for each patient, volume used for exchange, type of replacement, IV access used, complications, and outcome were reported. Results This series included 19 patients, 10 males, and 9 females, with a median age and weight of 76 months (IQR 18-121), and 20.9 kg. Improvement of the mean hemoglobin was observed from 5.3 ± 1.8 to 9.9 ± 2.6 g/dl at discharge. The average number of PE sessions was 2.4 sessions with no adverse effects encountered. The mean PICU stay was 16.6 days. Mortality occurred in 2 patients (10.5%) due to their primary illness, while 7 patients (36.8%) were in need of further immunotherapy, and 5 patients (28%) showed relapse. Conclusion PE may be used as a safe and successful therapy in children with severe acute life-threatening AIHA not responding to steroids, or if well-matched PRBCs are unavailable for transfusion.